2005
DOI: 10.1007/s00442-005-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation pulse use by an invasive woody legume: the role of soil texture and pulse size

Abstract: Plant metabolic activity in arid and semi-arid environments is largely tied to episodic precipitation events or "pulses". The ability of plants to take up and utilize rain pulses during the growing season in these water-limited ecosystems is determined in part by pulse timing, intensity and amount, and by hydrological properties of the soil that translate precipitation into plant-available soil moisture. We assessed the sensitivity of an invasive woody plant, velvet mesquite (Prosopis velutina Woot.), to large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 42 publications
2
85
0
Order By: Relevance
“…Many field experiments have imposed drought (Hanson et al, 2003;Wullschleger and Hanson, 2006;Beier et al, 2012) or described the impact of pulses of precipitation (Fravolini et al, 2005;Potts et al, 2006;Zeppel et al, 2008a;Resco et al, 2009). Here, we focus on seasonal changes in precipitation and extreme precipitation.…”
Section: Results Of Precipitation Timing Experimentsmentioning
confidence: 99%
“…Many field experiments have imposed drought (Hanson et al, 2003;Wullschleger and Hanson, 2006;Beier et al, 2012) or described the impact of pulses of precipitation (Fravolini et al, 2005;Potts et al, 2006;Zeppel et al, 2008a;Resco et al, 2009). Here, we focus on seasonal changes in precipitation and extreme precipitation.…”
Section: Results Of Precipitation Timing Experimentsmentioning
confidence: 99%
“…Rainfall is a key factor that controls dynamic changes in vegetation growth in arid and semi-arid regions as vegetation cover in those regions are extremely susceptible to the quantity, duration and frequency of rainfall (Fravolini et al, 2005;Liu et al, 2012;Gamon et al, 2013;Dutta et al, 2015;Kundu et al, 2015c). Past studies revealed that fluctuation of NDVI in drylands is consistent with spatial and temporal variations in rainfall (Fabricante et al, 2009;Kundu & Dutta, 2011;Kundu et al, 2015aKundu et al, ,b, 2016Kundu et al, , 2017.…”
Section: Introductionmentioning
confidence: 90%
“…In lightly grazed, high-productivity grasslands, grasses will initially be taller than woody plant seedlings, reducing light availability (de Dios et al 2014). Typically, grasses and woody seedlings in waterlimited environments share the same shallow soil horizon , so that grasses may furthermore monopolize soil resources to near exclusion of woody plant recruits, especially under environmental conditions that favor grasses: fine-texture or shallow soil sites with a summer rainy season characterized by small rainfall events that wet only the near-surface soils (Fravolini et al 2005). However, grazing reduces grass leaf area, root density, and depth and therefore competitive effects on seedlings above and below ground.…”
Section: Establishment Of Woody Plant Seedlingsmentioning
confidence: 99%
“…Many woody species have both a shallow, laterally extensive root system and deep taproots (Schenk and Jackson 2002). This reflects a generalist strategy for soil resource capture that allows them to use small rainfall events and the nutrients concentrated in the upper soil layers (Fravolini et al 2005), but to also access water and nutrients (e.g., NO 3 − ) percolated below the depths effectively exploited by grasses. Woody plants with this dimorphic root system can therefore exploit a wide range of growing season conditions (Scott et al 2006;Priyadarshini et al 2015).…”
Section: Topography and Soilsmentioning
confidence: 99%